2016
DOI: 10.4238/gmr15049070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miR-27a upregulation on thyroid cancer cells migration, invasion, and angiogenesis

Abstract: ABSTRACT. Thyroid cancer is the most common type of endocrine tumor. MicroRNAs (miRNAs) play a critical role in a variety of diseases, especially cancer occurrence and progression. However, the specific mechanism by which miRNAs trigger disease states has not been fully elucidated. This study aims to investigate the role of miR-27a in thyroid cancer cells. A wound healing assay was adopted to examine cell migration. A transwell assay was applied to assess cell invasion. A thyroid cancer xenograft model was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Among the four miRNAs measured, the strongest individual relationship to the development of left ventricular systolic dysfunction in the period up to 6 months after the myocardial infarction was shown by miR–27a [ 49 ]. What is interesting is, that miR–27a participates in the forming and spreading of many types of cancers, as confirmed in numerous research projects [ 50 59 ]. Among the four jointly assessed miRNAs mentioned above, a strong individual relationship to post-infarction left ventricular remodelling was also confirmed for miR–150.…”
Section: Mirna and Left Ventricular Remodellingmentioning
confidence: 87%
“…Among the four miRNAs measured, the strongest individual relationship to the development of left ventricular systolic dysfunction in the period up to 6 months after the myocardial infarction was shown by miR–27a [ 49 ]. What is interesting is, that miR–27a participates in the forming and spreading of many types of cancers, as confirmed in numerous research projects [ 50 59 ]. Among the four jointly assessed miRNAs mentioned above, a strong individual relationship to post-infarction left ventricular remodelling was also confirmed for miR–150.…”
Section: Mirna and Left Ventricular Remodellingmentioning
confidence: 87%
“…In the study, we found a key miR-27a-3p and its targeted Litaf might participate in the molecular mechanism of CIR. MiR-27a-3p has been identi ed to be implicated in several types of human malignancies, including thyroid cancer [38], breast cancer [39], gastric cancer [40] and esophageal cancer [41]. LITAF is a mediator of local and systemic in ammatory responses [42] and is locally upregulated in many in ammatory diseases, such as Crohn disease and ulcerative colitis [43].…”
Section: Discussionmentioning
confidence: 99%
“…When miR-27a was silenced with the help of a specific CD105 inhibitor, the level was maintained within 10%. These data suggest that miR-27a participates in angiogenesis; however, further research is necessary to better understand its molecular mechanism of action [19].…”
Section: Proangigenic Properties Of Micrornamentioning
confidence: 96%